2023
DOI: 10.1108/jbim-01-2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

Embracing green supply chain collaboration through technologies: the bridging role of advanced manufacturing technology

Abstract: Purpose The implementation of green collaboration has evolved from the interfirm level to the supply chain level, which requires more participation in information and manufacturing technologies. Despite many efforts to green supply chain collaboration (GSCC), the research on how to enhance it from a technological perspective remains unclear. Thus, this study aims to address this gap by exploring how to enhance green supplier, internal and customer collaboration through using information technology (IT) and adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…The findings also reveal a favorable effect of green supplier and customer integration on economic performance. Although Guo et al (2022) and Song et al (2017) postulated that GSCI would strengthen economic output, however, we found that green supplier integration fails to enhance economic performance (Akhtar et al, 2023). The reason may be that economic returns from green supplier integration may not be immediately apparent because of the higher upfront costs associated with green practices, such as investing in renewable energy sources and using eco-friendly materials.…”
Section: Hierarchical Regression On Green Customer Integrationmentioning
confidence: 59%
See 4 more Smart Citations
“…The findings also reveal a favorable effect of green supplier and customer integration on economic performance. Although Guo et al (2022) and Song et al (2017) postulated that GSCI would strengthen economic output, however, we found that green supplier integration fails to enhance economic performance (Akhtar et al, 2023). The reason may be that economic returns from green supplier integration may not be immediately apparent because of the higher upfront costs associated with green practices, such as investing in renewable energy sources and using eco-friendly materials.…”
Section: Hierarchical Regression On Green Customer Integrationmentioning
confidence: 59%
“…(2022) and Song et al. (2017) postulated that GSCI would strengthen economic output, however, we found that green supplier integration fails to enhance economic performance (Akhtar et al. , 2023).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations